Retrospective chart- review of Tetanus cases admitted in a tertiary care hospital
Background and Aims: Tetanus is a cause of thousands of death and disability annually in developing countries. Nepal is a low-income country and has achieved maternal-neonatal transmission elimination status. However, the literature regarding the status of generalized tetanus in adult populations is limited. This study was conducted to determine the clinical profile and outcome of patients with generalized tetanus. Methods: This was a retrospective study conducted among adult patients with generalized tetanus admitted at the Department of Internal Medicine or Department of Anesthesiology and Critical Care at B.P. Koirala Institute of Health Sciences, Dharan, Nepal from January 2012 to December 2016. Results: Of 40 patients with generalized tetanus, the mean age was 47